Desarrollo e implatación de un sistema multiplataforma para la automatización del centro director de tiro (CDT) para la escuela de artillería de la Fuerza Terrestre del Ecuador - Fuerte Militar Bolivar: Módulo II: Sistema para lanzadores de cohetes rusos: TATRA, BM-21, GRAD - 1P. - Córdova González, Vicente Francisco (2013)
This draft thesis chapters defined by the process of development and implementation of a multiplatform system for automating the Director of Shooting Center (CDT) for the School of Artillery of the Land Forces of Ecuador - Military Bolívar Fuerte to Russian Rocket Launchers : Treats, BM-21 Grad-1P; using agile development methodology eXtreme Programming.